2018
DOI: 10.1596/1813-9450-8651
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Medical Expenditures: Reflections on Three Issues

Abstract: The 'basic' approach to 'catastrophic' medical expenses (where expenses are related to consumption or income) indicates whether expenses cause a large percentage reduction in living standards. By contrast, the 'ability-to-pay approach' (where expenses are related to consumption or income less actual expenses on nonmedical necessities or an allowance for them) does not indicate whether expenses are large enough to undermine a household's ability to purchase nonmedical necessities. If the individual is a borrowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Households tend to smooth consumption over time by saving and borrowing (39), taking into account expected variations in income over the year, their assets and future earning potentials (38). Additionally, a policy paper suggested that consumption-based measure is more relevant in a lower-income setting where many households are borrowers, rather than savers (40). Therefore, we used annual household consumption as the basis to estimate household's ability to pay.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Households tend to smooth consumption over time by saving and borrowing (39), taking into account expected variations in income over the year, their assets and future earning potentials (38). Additionally, a policy paper suggested that consumption-based measure is more relevant in a lower-income setting where many households are borrowers, rather than savers (40). Therefore, we used annual household consumption as the basis to estimate household's ability to pay.…”
Section: Analysesmentioning
confidence: 99%
“…38 Additionally, a policy paper suggested that consumption-based measure is more relevant in a lower-income setting where many households are borrowers, rather than savers. 40 Therefore, we used annual household consumption as the basis to estimate household's ability to pay. The household consumption in each year was transformed into the value of 2010 based on the consumer price index 37 to adjust for inflation in the 8-year study period.…”
Section: Analysesmentioning
confidence: 99%